Bias-aware Teaching, Learning and Assessment - Hurford, Donna (Critical Practice in Higher Education., 2022)
With the spotlight on diversity and inclusion, this book offers university teachers informed and practical strategies for raising awareness of bias in teaching, learning and assessment practices and provides approaches to eliminate, limit and mitigate the negative effects of bias on university students.